Peningkatan Keterampilan Menulis dan Mendiseminasikan Karya Ilmiah hasil Penelitian Tindakan Kelas bagi Guru SMPN I Buduran Sidoarjo - Syahria, Nukmatus; Pramujiono, Agung; Yulia Rahayu, Endah; Nurjati, Nunung; Irawan, Nico; Poppy Handayani, Rosarina (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
Teachers are professionals who are not only required to be able to transfer their knowledge and educate students, but they must also be able to develop their professionalism, one of which is by conducting research. But in reality, teachers at SMPN I Buduran Sidoarjo have very little knowledge about research, especially classroom action research (CAR). The method chosen to overcome this problem is through workshops and PTK article mentoring clinics. The reason for choosing this method was to facilitate teachers at SMPN I Buduran Sidoarjo to practice directly in making CAR articles. The PTK article assistance workshop and clinic which was held on March 11 & 25 2023 was able to motivate teachers at SMPN I Buduran Sidoarjo to do CAR and help increase teachers' understanding of CAR implementation. And through the article assistance clinic, as many as 6 teachers have succeeded in publishing their articles in national journals. Keywords: scientific writing results of class action research; mentoring clinic for classroom action research articles; classroom action research workshop